Morphological awareness predicts the growth rate of Chinese character reading - Lin, Dan; Sun, Huilin; McBride, Catherine (Developmental science, 2019)
In this longitudinal study, we assessed 88 Hong Kong Chinese typically developing kindergarteners' Chinese character reading accuracy four times with 6‐month intervals over 1.5 years with the first testing point in the fall of the second year of kindergarten (K2), during which morphological awareness, phonological awareness, orthographic awareness, visual–spatial relationships, and nonverbal IQ were tested (Time 1). The latent growth curve modeling showed that reading development in Chinese of typically developing kindergarteners followed a cumulative linear trajectory, suggesting that children with higher initial reading ability develop reading ability at a faster rate. Additionally, morphological awareness at K2 positively and uniquely predicted a linear growth pattern of character reading between K2 and K3 over 1.5 years, a period in which formal teaching and learning Chinese takes place in Hong Kong. Contributing to the literature, these findings highlighted the unique significance of morphological awareness in the growth rate of reading: Typically developing children with better early morphological awareness tend to have a higher initial point of reading ability and, more importantly, a faster growth rate, resulting in a wider discrepancy of developmental outcomes between low‐ and high‐ performers. The results suggest that greater attention should be focused on the development of morphological awareness in early readers, given its salient role in Chinese reading development. Early morphological awareness uniquely predicted the growth rate of the following Chinese character reading among Chinese kindergartners with initial reading ability, nonverbal reasoning, visual‐spatial skills, phonological awareness, and orthographic awareness controlled. The observed trajectory of character reading from T1 to T4 of two representative children: The one in bolded solid line scored high in MA at T1; the one in bolded dotted line scored low in MA at T1.